The Effect of Altman Z-Score Model on Financial Distress to the Rural Banks of West Kalimantan Province - PERTIWI, URAY MAHARANI (Jurnal Manajemen Update, 2018)
Financial distress is the company's financial condition in the stage of decline before liquidation or bankruptcy of the company (Ali, 2009). In general, financial distress is a condition where companies experience financial difficulties and are threatened with bankruptcy. Then the condition of financial distress needs to be watched out for the company. This study aims to examine the effect of the Altman Z-SCORE ratio, namely the ratio of Net Working Capital to Total Assets (WCTA), Retained Earning to Total Assets (RETA), Earning Before Interest and Tax to Total Assets (EBITTA), and Book Value of Equity to Total Liability (BVETL) to Financial Distress proxied by Z-Score Modification at the Rural Bank of West Kalimantan Province and to find out the condition of financial distress in each bank calculated by the modified Altman Z-score method. This study took a five-year observation period, from 2012 to 2016, where the number of samples used was as many as 15 companies crediting the rural banks of West Kalimantan Province. This study examines the regression relationship between the dependent variable and the independent variable with multiple linear regression. In this study showed that the partial test results of the ratio found in the modified Altman Z-score, WCTA, RETA, EBITTA and BVETL had a significant positive effect on financial distress.Keywords: Financial Distress, Z-Score, BPR, WCTA, RETA, EBITTA, BVETL